1971
DOI: 10.1113/jphysiol.1971.sp009687
|View full text |Cite
|
Sign up to set email alerts
|

The fine structural localization of cholinesterases in the carotid body of the cat

Abstract: 1. The distribution of cholinesterases in the carotid body of the cat has been investigated with the electron microscope to obtain a clearer picture of the localization of the enzyme. This is of relevance to the possible role of acetylcholine as a transmitter in the carotid body. 2. Tissues were fixed for short periods and incubated by the method of Karnovsky for the fine localization of cholinesterases. 3. The enzyme was found in two main sites. Butyrylcholinesterase was present on the type II cell membrane w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In support of its role in transmission, however, ACh is found within the carotid body (273, 440) together with choline acetyltransferase, the rate-limiting enzyme for ACh synthesis, in rat (626), cat and rabbit (883), and its degradative enzyme, cholinesterase, (51, 84). The content of ACh has been estimated at 5.6 p mol/carotid body and was little changed following sinus nerve section, which was taken to indicate that ACh was not significantly localized within afferent nerve endings (273) and is most likely stored within the clear vesicles of type I cells.…”
Section: Neurotransmission In the Carotid Bodymentioning
confidence: 99%
“…In support of its role in transmission, however, ACh is found within the carotid body (273, 440) together with choline acetyltransferase, the rate-limiting enzyme for ACh synthesis, in rat (626), cat and rabbit (883), and its degradative enzyme, cholinesterase, (51, 84). The content of ACh has been estimated at 5.6 p mol/carotid body and was little changed following sinus nerve section, which was taken to indicate that ACh was not significantly localized within afferent nerve endings (273) and is most likely stored within the clear vesicles of type I cells.…”
Section: Neurotransmission In the Carotid Bodymentioning
confidence: 99%
“…This article must therefore be hereby marked the occurrence of AcCho (25,) and acetylcholinesterase (32,33) (11) and most probably store NE (39,41).…”
Section: Innervation Of Glomus Cells: Afferent And/or Efferent?mentioning
confidence: 99%
“…In the ensuing decades, numerous studies investigated the role of ACh in chemosensation and demonstrated that small quantities of cholinergic agonists and antagonists profoundly altered chemoreceptor discharge 20. Neurochemical investigations indicated that the metabolic machinery necessary for ACh synthesis, storage and inactivation appear to be associated with type I cells in the carotid body 2,3,23,24,31,35,36 and that afferent fibers of the CSN are nearly devoid of cholinergic activity23, 28. In addition, it has been demonstrated that an ACh-like substance is released upon stimulation of the organ in vitrol7, Is.…”
Section: Introductionmentioning
confidence: 99%